Challenges and prospects for the formation of state policy in the field of cybersecurity and combating cybercrime - Savchuk, Serhii (Public Policy and Accounting, 2024)
Cyberattacks aimed at disrupting the functioning of critical infrastructure, spreading disinformation, and stealing personal data and financial resources pose significant risks to states' national security. The purpose of the study is to substantiate the challenges Ukraine faces in ensuring cybersecurity, particularly in the context of hybrid warfare, and to determine the prospects for the formation of state policy in cybersecurity and combating cybercrime. The paper highlights the main threats arising in cyberspace, their impact on society, the economy, and state institutions, and the factors ensuring counteraction to cybercrime. The main types of cyberattacks used by intruders against other states are systematized and grouped according to the relevant features. Particular attention is paid to the prospects for the formation of an effective state policy in the field of cybersecurity. The author identifies the key directions for improving the legislative framework, strengthening technical capabilities for monitoring and responding to cyber threats, and increasing the level of international cooperation and coordination with other countries and international organizations. It is proved that an effective state policy in the field of cybersecurity should be based on a comprehensive and systematic approach that takes into account both internal and external challenges and integrates the best international practices of implementing modern information security technologies.